2005
DOI: 10.1080/j.0001-6349.2005.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide increases endocervical secretion at the ovulatory phase in the female

Abstract: The results suggest that glandular NO production increases cervical secretion. Thus, cervical secretion may, apart from hormonal regulation, be influenced by the autonomic nervous system, and in addition, NO may be a prerequisite for this influence. This in turn may have implications on fertilization and fertility regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Honey also contains nitric oxide (NO) metabolites, which may be responsible for some of the biologic and therapeutic effects of honey [19]. A physiologic level of NO has been found to be important for sperm motility, capacitation, and acrosome reaction [20,21], and it may also be that NO has a positive effect on the quality and quantity of the ovulatory cervical mucus [22]. The amino acid content of both honey and royal jelly may play a role as well, either by enhancing acrosome reaction and sperm motility or by improving fertilization [23]; and sperm motility may be further enhanced by the short‐chain fatty acids specific of royal jelly, especially 10‐hydroxy‐2‐decenoic acid [24].…”
Section: Discussionmentioning
confidence: 99%
“…Honey also contains nitric oxide (NO) metabolites, which may be responsible for some of the biologic and therapeutic effects of honey [19]. A physiologic level of NO has been found to be important for sperm motility, capacitation, and acrosome reaction [20,21], and it may also be that NO has a positive effect on the quality and quantity of the ovulatory cervical mucus [22]. The amino acid content of both honey and royal jelly may play a role as well, either by enhancing acrosome reaction and sperm motility or by improving fertilization [23]; and sperm motility may be further enhanced by the short‐chain fatty acids specific of royal jelly, especially 10‐hydroxy‐2‐decenoic acid [24].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Nitric oxide has been demonstrated to play an essential role in reproduction and various adverse reproductive outcomes have been reported with defective nitric oxide synthesis. [9][10][11][12] Previous studies have confirmed the role of nitric oxide in adjustment of uterine blood flow. A sixty percent reduction in uterine artery blood flow has been demonstrated with nitric oxide inhibitor, while a favorable effect on sub-endometrial blood flow has been reported with nitric oxide donors.…”
Section: Introductionmentioning
confidence: 84%
“…12 It is postulated that FertileCM enhances cervical mucus because it contains L-arginine-a precursor to nitric oxide-a molecule responsible for the autonomic cholinergic nervous modulation of cervical mucus secretion. 13 Data generated by T. Hilgers shows that mucus enhancers improve mucus cycle scores. 14 For example, in a group of eleven patients taking amoxicillin during the fertile window, mucus cycles scores went from an average of 4.0 to an average score of 9 (p ϭ 0.003).…”
Section: Treatmentmentioning
confidence: 99%